Community Empowerment: Interpreting Election for Baduy Indigenous People - Al Arif Fitriana, Mohamad Noor Fajar (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2024)
This research explores the unique perspective of the Baduy indigenous community onIndonesian elections. While voting is a constitutional right for all citizens, the Baduy peopleview the electoral process through the lens of their deeply rooted cultural philosophy. Theyadhere to the principle of lunang (